COVID-19 and dengue coinfection in Latin America: A systematic review - León-Figueroa, Darwin A. (2022)
“Introduction: Coronavirus Disease 2019 (COVID-19) caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) has spread globally, becoming a long-lasting pandemic. Dengue is the most common arboviral disease in tropical and subtropical regions worldwide. COVID-19 and dengue coinfections have been reported, associated with worse outcomes with significant morbidity and mortality. Therefore, this study aims to determine the epidemiological situation of COVID-19 and dengue coinfection in Latin America. Methods: A systematic literature review was performed using PubMed, Scopus, Embase, Web of Science, LILACS, and BVS databases from January 1, 2020, to September 4, 2021. The key search terms used were ““dengue““ and ““COVID-19““. Results: Nineteen published articles were included. The studies were case reports with a detailed description of the coinfection’s clinical, laboratory, diagnostic, and treatment features. Conclusion: Coinfection with SARS-CoV-2 and dengue virus is associated with worse outcomes with significant morbidity and mortality. The similar clinical and laboratory features of each infection are a challenge in accurately diagnosing and treating cases. Establishing an early diagnosis could be the answer to reducing the estimated significant burden of these conditions.“